The student’s professional development through the partnership between technical schools and companies - Cimarelli , Carine; Velloso, Larissa Cimarelli (Seven Editora, 2024)
The article demonstrates, through the practice of a TCC project, the importance of Technical Schools establishing partnerships with companies in the city where students can develop projects to, through studies on problem situations that the company may have, propose solutions that help it neutralize or minimize these impasses. It also demonstrates that the experience of high school and technical students in the administrative activities of a company provides significant skills in students to work in the job market, based on a TCC project focused on the Quality of Life of the employees of the partner company aiming at improving and increasing productivity. The project was carried out with students from the Technical Education Integrated to High School in Administration at Etec de Itararé, through the Development of the Course Completion Work component, relating theoretical and practical knowledge of People Management and Physical Education, from the Common Base of High School, in addition to a partnership with the Nutrition and Dietetics course and with the company Fort Paletes de Itararé. With the results obtained, it is possible to perceive the importance of pedagogical practices applied outside the school environment with partner companies, bringing students closer to the job market even before completing high school, so that they develop essential skills for their professional success. DOI:https://doi.org/10.56238/sevened2024.026-023